Pendidikan Kejuruan Tata Busana sebagai Katalisator Kewirausahaan: Studi Kasus Usaha Konveksi Hareem Collektion Pesantren Husnul Hidayah Kemasantani, Gondang, Mojokerto - Nasihin, Fikri Zainun (FADZAT: Jurnal Ekonomi Syariah, 2023)
This study explores the role of vocational education in fashion design as a catalyst for entrepreneurship, focusing on the case study of Hareem Collektion, a convection business initiative under the auspices of a Vocational High School's Fashion Department. The research highlights the integration of theoretical knowledge and practical application in fostering entrepreneurial skills among students. Through a qualitative analysis of the Hareem Collektion initiative, findings reveal that hands-on experience in a real-world business setting significantly enhances students' understanding of the fashion industry's challenges and opportunities. The study underscores the importance of industry-education collaboration, project-based learning, and the incorporation of sustainability and technology into the curriculum to prepare students for the dynamic and competitive fashion industry. Policy implications and recommendations are provided to optimize vocational education's potential in nurturing future entrepreneurs in fashion. This research contributes to the discourse on vocational education's impact on entrepreneurship, offering insights into effective strategies for equipping students with the necessary skills and mindset for innovation and business success in the fashion sector.